Avaliação de deformidades morfológicas em larvas de Chironomus (Diptera, Chironomidae) na bacia do rio Piracicaba e sua aplicação no biomonitoramento - Bonani, Fabiana (2010)
The Piracicaba river basin is considered one of the most polluted in the state of São Paulo. It is located in a region with high population density in addition to great development of agribusiness and chemical, textiles, metals, electronics, automotive and paper industries. The objective of this study was to analyze the incidence of morphological deformities in the mentum of Chironomus larvae of this basin, especially in the basin of Quilombo stream. Physical and chemical analysis were performed in water and sediment, ecotoxicological and mutagenicity tests and analysis of the benthic community at ten sampling sites in August 2007. The influence of domestic sewage in the sampling sites was evidenced by analysis of surface and bottom water, which in general, gave results outside the limits established by CONAMA Resolution 357/2005. In the sediment it was detected the presence of metals and PAHs at higher concentrations than the limits established by CONAMA Resolution 344/04, besides the acute toxicity to Chironomus sancticaroli and Hyalella azteca larvae. The best environmental condition for the benthic community was observed in Jacuba stream and Piracicaba river, upstream of the Quilombo stream, which corresponds to the most preserved area. The major incidence of morphological deformities in the mentum of Chironomus evaluated in sediment samples were observed at two points located in the Piracicaba river (Points 2 and 3), downstream of the Quilombo stream, with 25.3% and 36.3% of deformities, respectively, and the lack of teeth was the most common type of deformity. In terms of environmental quality, Chironomus larvae collected in vegetation offered an additional parameter for some sites, because the sediment offered no significant number of larvae. In most of sampling sites it was not observed a direct correlation between the frequency of gross deformities and the level of contaminants, with the exception of zinc. It is suggested the value of 2% for the limit of natural incidence of deformities in non-impacted environments. Further investigations should be conducted in reference sites in the country, with the objective to include this variable in monitoring programs of environmental quality.